Review of pharmacological and surgical treatment options of uveitic glaucoma - Łazicka-Gałecka, Monika; Guszkowska, Maria; Gałecki, Tomasz; Dziedziak, Jacek; Kamińska, Anna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
The treatment of uveitic glaucoma (UG) is a very complex issue. The choice of an appropriate therapeutic approach depends primarily on determining the pathomechanisms responsible for the increase in intraocular pressure (IOP), but also on establishing the correct diagnosis of the underlying pathology. The first-line treatment of IOP elevation in patients with uveitis is pharmacotherapy based on the concomitant use of anti-inflammatory and IOP-lowering agents. The most commonly used topical treatment options include β-blockers and carbonic anhydrase inhibitors (CAIs). When choosing an active substance, care should always be taken to ensure that the treatment is tailored to the baseline IOP and to the patient's underlying disease and health status. The use of prostaglandin analogues in the treatment of patients with UG remains a controversial issue. Numerous studies are currently underway to evaluate the safety of new drug groups, including Rho kinase inhibitors. In approximately 30% of patients with UG pharmacological treatment is insufficient and surgical intervention is required. The current gold standard in the operative treatment of UG is trabeculectomy, but because of the unpredictability of outcomes and invasiveness of the technique, multiple attempts are made to use less invasive surgical modalities. In the most severe cases of UG, which are refractory to standard therapies, cyclodestructive procedures are employed. They achieve an IOP-lowering effect through damage to the ciliary body using a laser or low temperature. Despite being effective at reducing the IOP, cyclodestructive modalities may be associated with severe complications. The cornerstone of the management of narrow- and closed-angle uveitic glaucoma is laser iridotomy. However, it must be kept in mind that an active inflammation may shorten the duration of its patency. The management of patients with UG requires striking a balance between appropriate concomitant anti-inflammatory and IOP-lowering treatment to be able to stop progressive optic nerve damage.